[68Ga]Ga-NODAGA-TriGalactan, a low molecular weight tracer for the non-invasive imaging of the functional liver reserve - Maximilian A. Zierke; Christine Rangger; Kimia Samadikhah; Marlene Panzer; Stefanie Dichtl; Nikolas Hörmann; Doris Wilflingseder; Andreas M. Schmid; Roland Haubner (SpringerOpen, 2024)
Abstract Background Determination of the functional liver mass is important in a variety of clinical settings including liver surgery and transplantation. [99mTc]Tc-diethylenetriamine-pentaacetic acid galactosyl human serum albumin (99mTc-GSA) is a radiotracer targeting the asialoglycoprotein receptor (ASGR) and is routinely used in Japan for this purpose. Here we describe the development and evaluation of [68Ga]Ga-NODAGA-TriGalactan a low molecular weight PET-tracer targeting this structure. Results For synthesis TRIS as branching unit and NODAGA as chelator for labelling with [68Ga]Ga are included. Three galactose moieties are conjugated via a click chemistry approach resulting in the desired labelling precursor.68Ga-labelling could be accomplished in high radiochemical yield and purity. [68Ga]Ga-NODAGA-TriGalactan is very hydrophilic and revealed high plasma stability and low plasma protein binding. Fluorescence imaging showed binding on ASGR-positive organoids and the IC50-value was in the nanomolar range. Most importantly, both biodistribution as well as animal imaging studies using normal mice demonstrated high liver uptake with rapid elimination from all other organs leading to even higher liver-to-background ratios as found for 99mTc-GSA. Conclusion [68Ga]Ga-NODAGA-TriGalactan shows high in vitro stability and selectively binds to the ASGR allowing imaging of the functional liver mass with high contrast. Thus, our first generation compound resulted already in an alternative to 99mTc-GSA for imaging the functional liver reserve and might allow the broader use of this imaging technique.